The Run of the Red Queen: Government, Innovation, Globalization, and Economic Growth in China - Breznitz, Dan; Murphree, Michael (Yale University Press, 2011)
Few observers are unimpressed by the economic ambition of China or by the nation's remarkable rate of growth. But what does the future hold? This meticulously researched book closely examines the strengths and weaknesses of the Chinese economic system to discover where the nation may be headed and what the Chinese experience reveals about emerging market economies. The authors find that contrary to popular belief, cutting edge innovation is not a prerequisite for sustained economic vitality-and that China is a perfect case in point.